Yield and Profitability of Sweet Potato (Ipomoea batatas (L.) Lam) as a Function of Increasing Levels of Phosphorus and Varieties in Southern Ethiopia. (18th March 2023) - Dawit, Mesfin; Habte, Abera
Abstract : Sweet potato is among the most important food security crops in Ethiopia. However, its productivity is constrained by poor soil fertility and a lack of improved varieties. A field experiment was conducted to evaluate the growth and yield response and profitability of three sweet potato varieties to rates of phosphorus (P) in Southern Ethiopia. Five rates of P (0, 10, 20, 30, and 40 kg ha −1 ) and three sweet potato varieties (Awassa-83, Kulfo, and Local) were considered as treatments that were laid out in a randomized complete block design with three replications. The vine length, internodes length, diameter, and the number of vines were significantly varied among varieties while P had a nonsignificant effect on these parameters. The tuber yield of sweet potato was influenced by the combined effect of variety and P rate. The highest marketable yield (30.22 t ha −1 ) was obtained at 30 kg P ha −1 from variety Awassa-83 and the lowest marketable yield (6.57 t ha −1 ) was obtained from Kulfo at 0 kg P ha −1 . Thus, improvement of sweet potato productivity in the study area could be achieved through the use of Awassa-83 variety with P at a rate of 10 kg ha −1 .